STUDI PENENTUAN STRUKTUR LAPISAN BATUAN DI DESA PADAELO’ KECAMATAN MALLAWA KABUPATEN MAROS SULAWESI SELATAN - Rahmaniah, Rahmaniah; Hernawati, Hernawati; Nurvadillah, Nurvadillah; Aliasra, A Fany; Irmayanti, Irmayanti; Mulia, Ayu (Universitas Islam Negeri Alauddin Makassar, 2019)
It has been done field lecture with the title of study of rock structural layer in the village in the district Elo Mallawa Maros South Sulawesi Regency. The purpose of this field of lecture is to determine the structure of rock lining at the site of field lecture. The methods used in the course of this field are the methods of discussion, sampling and measurement. The tools used are geological compass, meter, hammer geology, GPS and ATK. Results obtained in the location of the lecture field is the presence of production stones consisting of several types of rock layers. The types of rock layers acquired are Rijang stone, sandstone, stone clay, and limestone. And the obtained stone layer has a strike and a dip N 353° E 64°.